Genetic Predictors for Sinusoidal Obstruction Syndrome—A Systematic Review - Waespe, Nicolas (J Pers Med, 2021)
Sinusoidal obstruction syndrome (SOS) is a potentially life-threatening complication after hematopoietic stem cell transplantation (HSCT) or antineoplastic treatment without HSCT. Genetic variants were investigated for their association with SOS, but the evidence is inconclusive. We performed a systematic literature review to identify genes, gene variants, and methods of association analyses of genetic markers with SOS. We identified 23 studies after HSCT and 4 studies after antineoplastic treatment without HSCT. One study (4%) performed whole-exome sequencing (WES) and replicated the analysis in an independent cohort, 26 used a candidate-gene approach. Three studies included >200 participants (11%), and six were of high quality (22%). Variants in 34 genes were tested in candidate gene studies after HSCT. Variants in GSTA1 were associated with SOS in three studies, MTHFR in two, and CPS1, CTH, CYP2B6, GSTM1, GSTP1, HFE, and HPSE in one study each. UGT2B10 and LNPK variants were identified in a WES analysis. After exposure to antineoplastic agents without HSCT, variants in six genes were tested and only GSTM1 was associated with SOS. There was a substantial heterogeneity of populations within and between studies. Future research should be based on sufficiently large homogenous samples, adjust for covariates, and replicate findings in independent cohorts.